PENCATATAN ANAK LUAR KAWIN SETELAH PUTUSAN MAHKAMAH KONSTITUSI NO.46/PUU-VIII/2010 - Wahyuni S.H., M.H. (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
The presence of a child creates happiness and well-being for its family for children are the fruit of marriage and as descentfoundation. However, there also a condition in which presence of child is not always a joy. This usually happens when a child is born outside of legal marriage. The child birth outside of marriage is not only caused by an extramarital affair, in a certain circumstances can also give birth outside of marriage, such as the implementation of marriages which only performed by custom / religion, and does not include the father's name per se would cause problems for child. Based on this reality, Constitutional Court makes a decision NO.46/PUUVIII/2010 that children whom born of anunrecorded marriage may have a civil relationship with his or her father as long as legally can prove his or her origin based on science and technology and / or other evidence have a blood relationship, including civil relationship with his family. This will imply that the child can be listed with name of his or her father. In practice, the Constitutional Court's decision faced many obstacles, namely the cultural distinguish between legitimate and illegitimate children, ignorance about requirements that must be met to register the birth of child, the difficulty for obtaining evidence in the scientific and technological as well as the lack of regulations that can be used as guidelines to implement the Constitution Court's decision.